Liberia : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Liberia. (IMF Staff Country Reports; Country Report, 2016)
This 2016 Article IV Consultation highlights that the Ebola epidemic and the fall in commodity prices have revealed the vulnerabilities of Liberia's economy. After barely positive growth in 2014, GDP was flat in 2015 mainly owing to the decline in activity in the iron ore and rubber sectors. Although international gross reserves increased in 2015, the Central Bank of Liberia's net foreign exchange position declined owing to operational deficits and exceptional support to the banking sector. In 2016, growth is expected to rise to 2.5 percent, thanks to a rebound in services and the start of gold production, while inflation should stay in the single digits.